Adaptação transcultural do formulário POLST: Physician Orders for Life-Sustaining Treatment - Mayoral, Vânia Ferreira de Sá [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
No Brasil atual a maior parte dos profissionais e instituições de saúde ainda se encontram longe de constituírem uma rotina de discussão sobre preferências de cuidados no fim da vida junto a pacientes com prognóstico reservado. Esta corresponde a uma grande lacuna na atenção à saúde em nosso país, a qual frequentemente se associa a sofrimento evitável de pacientes e familiares. Em 1991 nos EUA foi iniciado um programa de discussão de preferências de cuidados no fim da vida denominado POLST (Physician Orders for Life-Sustaining Treatment). Trata-se de um sistema coordenado para evocar, documentar e comunicar as preferências de pacientes/familiares quanto a tratamentos prolongadores da vida para enfermos com expectativa de vida reduzida. Atualmente o POLST representa uma das melhor sucedidas estratégias para a elicitação e documentação de preferências de cuidados no fim da vida naquele país. O objetivo dessa pesquisa foi realizar a Adaptação Transcultural (ATC) do formulário POLST para o contexto brasileiro. A metodologia de ATC baseou-se nas recomendações da International Society for Pharmacoeconomics and Outcomes Research. Foram realizadas 3 traduções diretas e independentes do instrumento fonte para o português, as quais passaram por uma reunião de reconciliação de forma a gerar uma versão síntese. Essa versão foi submetida a duas traduções reversas para o inglês e posteriormente foi realizado um teste piloto do formulário com 20 médicos e 10 pacientes. Versões do instrumento foram apresentadas a membros do Comitê Nacional do POLST nos EUA e discutidas com uma especialista em direito e dois especialistas em bioética. Finalmente foi alcançada uma versão do formulário POLST adaptada para o Brasil. Trata-se da primeira ATC desse instrumento para além das fronteiras dos EUA. A ATC desse formulário representa o primeiro passo para sua futura implantação no Brasil, a qual irá demandar sua apresentação ao Conselho Federal de Medicina e a pactuação de seu uso entre diversos atores sociais (ex. Hospitais, Serviços de Urgência Pré-hospitalar e Rede de Atenção Primária à Saúde). Espera-se que no longo prazo o resultado desse trabalho contribua para uma melhor atenção à saúde no fim da vida no Brasil e sirva de estímulo para novos processos de ATC do POLST em outros países.

In Brazil most health care professionals and institutions still have not included discussions about preferences of care at the end of life with patients with decreased life expectancy as part of their daily routine. This represents a major gap for the care at the close of life in Brazil that is frequently associated with avoidable suffering of patients and their loved ones. In 1991 the Physician Orders for Life-Sustaining Treatment (POLST) program was started in the USA. It embodies a coordinated system to elicit, record and communicate patients’ and families’ preferences about life-prolonging treatments for individuals with decreased life expectancy across a variety of health care settings. The POLST paradigm has spread across the USA and currently represents one of the most successful strategies to elicit and record preferences of care at the end of life in that country. The present research aimed to conduct the Cross-Cultural Adaptation (CCA) of the POLST form to the Brazilian context. The cross-cultural adaptation methodology was based on the principles of good practice for the translation and cultural adaptation process recommended by the International Society for Pharmacoeconomics and Outcomes Research. Three independent direct translations of the source instrument to Portuguese were performed. Those translations were synthesized into a single version after a reconciliation meeting. Two independent native English speakers performed 2 back translations of that version into English. We pilot tested the form under adaptation with 20 physicians and 10 patients. Versions of the instrument were discussed with members of the National POLST Paradigm Task Force. The form was also discussed with an attorney and 2 specialists in Bioethics. Finally we arrived at a cross-culturally adapted version of the POLST form for Brazil. This is the first CCA of the POLST form for use beyond the borders of the USA. The CCA of this form represents the first step for its future implantation in Brazil, which will require the presentation of the POLST Paradigm to the Brazilian Federal Medical Council and a set of agreements among a variety of social stakeholders (e.g., Hospitals, Pre-hospital Emergency Systems, and Primary Care Units). We hope that in the long term the result of the present research will contribute to improvements in the care at the end of life in Brazil and that it may foster new CCA initiatives of the POLST form in other countries.
Cross-Cultural Adaptation of the POLST (Physician Orders for Life-Sustaining Treatment) form to Brazil
Keywords: Diretivas antecipadas; Planejamento antecipado de cuidados; Cuidados paliativos; Advance directives; Advance care planning; Palliative care